2013
DOI: 10.1002/pmic.201200230
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis revealed the altered tear protein profile in a rabbit model of Sjögren's syndrome-associated dry eye

Abstract: Sjögren’s syndrome (SS) is an autoimmune disease which results in pathological dryness of mouth and eye. The diagnosis of SS depends on both clinical evaluation and specific antibodies. The goal of this study was to use quantitative proteomics to investigate changes in tear proteins in a rabbit model of SS-associated dry eye, induced autoimmune dacryoadenitis (IAD). Proteomic analysis was performed by iTRAQ and nanoLC-MS/MS on tears collected from the ocular surface, and specific proteins were verified by high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…Zhou et al [576] have reported on similarities to human dry eye tear protein expression in a rabbit model of Sjögren syndrome-associated dry eye induced autoimmune dacryoadenitis (Table 10). The expression of S100A6, S100A9, and serum albumin was upregulated in this model, whereas TF, PIP, polymeric immunoglobulin receptor (pIgR) and Ig gamma chain C region were downregulated.…”
Section: Translational Dry Eye Animal Models Of Tear Filmmentioning
confidence: 99%
“…Zhou et al [576] have reported on similarities to human dry eye tear protein expression in a rabbit model of Sjögren syndrome-associated dry eye induced autoimmune dacryoadenitis (Table 10). The expression of S100A6, S100A9, and serum albumin was upregulated in this model, whereas TF, PIP, polymeric immunoglobulin receptor (pIgR) and Ig gamma chain C region were downregulated.…”
Section: Translational Dry Eye Animal Models Of Tear Filmmentioning
confidence: 99%
“…21 As a first-line vertebrate immune defense, the polymeric immunoglobulin receptor transports polymeric IgA and IgM across the epithelium to mucosal secretions, whereby the cleaved ectodomain becomes a component of secretory antibodies or when the unbound ligand form binds and excludes bacteria. 22 The fact that inflammation-associated proteins were downregulated after treatment indicates that a regional inhibitory inflammatory reaction occurred.…”
mentioning
confidence: 99%
“…A number of studies have verified these basic proteomic findings [10][11][12]. Furthermore, a similar change in the tear proteome was also observed in a rabbit model of Sjögren's syndrome-associated dry eye [13]. Proteomic studies have consistently found that levels of proinflammatory proteins indicating ocular surface inflammation were marked by well-known inflammation-related proteins (S100 A8 and S100 A9) [14].…”
mentioning
confidence: 61%